Animal Meat Speciation Methods for Adulteration Identification - Sakha, Mohammad Zaher (Journal of Natural Sciences – Kabul University, 2025)
Humans have always used animal meat as a food resource to obtain balanced energy. Meat contains essential materials such as amino acids, fats, vitamins, minerals, and other vital components that play a crucial role in human biological functions and structure. Various food frauds occur in different food products worldwide; however, meat is no exception. There are different methods for meat speciation to identify adulteration, which include physical, chemical, and biological analysis. Each of these methods has its own sensitivity and precision. By reviewing several tests, it is clear that biological and molecular methods, such as PCR and ELISA, are more sensitive and accurate compared to other tests. These two methods are frequently and widely used for meat speciation in cases of doubt.